2005
DOI: 10.1136/bjsm.2005.020909
|View full text |Cite
|
Sign up to set email alerts
|

A controlled clinical pilot trial to study the effectiveness of ice as a supplement to the exercise programme for the management of lateral elbow tendinopathy

Abstract: Background:The use of ice as a supplement to an exercise programme has been recommended for the management of lateral elbow tendinopathy (LET). No studies have examined its effectiveness.Objectives:To investigate whether an exercise programme supplemented with ice is more successful than the exercise programme alone in treating patients with LET.Methods:Patients with unilateral LET for at least four weeks were included in this pilot study. They were sequentially allocated to receive five times a week for four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 44 publications
0
54
0
6
Order By: Relevance
“…The exercise programme in both groups was carried out in home. Although a home exercise programme can be performed any time during the day without requiring supervision from a therapist, our clinical experience has shown that patients fail to comply with the regimen of home exercise programmes [20]. Although many ways can be recommended to improve the compliance of patients with the home exercise programme such as phone calls, exercise monitors and better self -management education, it is believed that this problem can be really solved by the supervised exercise programmes performed in a clinical setting under the supervision of a therapist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exercise programme in both groups was carried out in home. Although a home exercise programme can be performed any time during the day without requiring supervision from a therapist, our clinical experience has shown that patients fail to comply with the regimen of home exercise programmes [20]. Although many ways can be recommended to improve the compliance of patients with the home exercise programme such as phone calls, exercise monitors and better self -management education, it is believed that this problem can be really solved by the supervised exercise programmes performed in a clinical setting under the supervision of a therapist.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, eccentric exercises were performed at a low speed in every treatment session because this allows tissue healing [4]. Ice was recommended at the end of the treatment but research has shown that ice as a supplement to an eccentric exercise programme offers no benefit to patients with tendinopathy [20]. Finally, the avoidance of painful activities is crucial for tendon healing, because training during the treatment period increases patients' symptoms and delays tendon healing [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sobre la base de los criterios de selección de nuestra RS, sólo 36 artículos fueron incluidos (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)27,29,31,(33)(34)(37)(38)(39)(40)(43)(44)(45)61,(73)(74)(75)(82)(83)(84). El riesgo de sesgo se evaluará utilizando la herramienta propuesta en el "Cochrane Handbook" para Ensayos Clínicos Aleatorizados (91).…”
Section: Evaluación Del Riesgo De Sesgo De Los Artículos Seleccionadosunclassified
“…Es necesario establecer que existe una evidencia insuficiente con respecto a su efectividad a largo plazo (43) . Pero cabe destacar, que por más que existan tratamientos con diferentes mecanismos teóricos de acción, todos tienen un mismo objetivo, en reducir el dolor y mejorar la función (44). Sin embargo; estudios han señalado que a pesar de la resolución de síntomas mediante tratamientos conservadores permanece el déficit sensoriomotor (45), cuyas alteraciones se encuentran presentes de forma bilateral en pacientes con EL (46,47).…”
Section: Introductionunclassified